Concepts and strategies on how to train and motivate teachers to implement a kindergarten‐based, family‐involved intervention to prevent obesity in early childhood. The ToyBox‐study. (August 2014) - Payr, A.; Birnbaum, J.; Wildgruber, A.; Kreichauf, S.; Androutsos, O.; Lateva, M.; De Decker, E.; De Craemer, M.; Iotova, V.; Manios, Y.; Koletzko, B.; ,
Summary: The key person for the implementation of kindergarten‐based behavioural interventions is the kindergarten teacher. When conducting intervention studies in kindergartens, training sessions are needed to train and motivate kindergarten teachers for programme implementation. This paper presents the systematic development of the teachers' trainings executed in the ToyBox‐intervention – a kindergarten‐based and family‐involved obesity prevention programme for children aged 4–6. Based on concepts for the education of kindergarten teachers, on general strategies for successful programme implementation and on the ToyBox programme‐specific requirements, the aims of the teachers' trainings were defined and an overall concept was deduced. Regarding the concept for the ToyBox teachers' training sessions, it is concluded that the training modules should focus on presenting information on the practical implementation of the intervention. Furthermore, these modules should also include self‐efficacy enhancing components and should give kindergarten teachers opportunities to share experiences. Regarding the didactic methods applied in the ToyBox teachers' training sessions, constructivist learning approaches that facilitate active participation, reflective thinking and personal involvement were implemented. Emphasis was put not only on the content but especially on the didactic methods of teachers' trainings in order to enhance devotion to, and quality and sustainability of the ToyBox‐intervention.